2022
DOI: 10.3389/fphar.2022.1043975
|View full text |Cite
|
Sign up to set email alerts
|

Receptor activator of nuclear factor-κB ligand-mediated osteoclastogenesis signaling pathway and related therapeutic natural compounds

Abstract: Osteoclast is a hematopoietic precursor cell derived from the mononuclear macrophage cell line, which is the only cell with bone resorption function. Its abnormal activation can cause serious osteolysis related diseases such as rheumatoid arthritis, Paget’s disease and osteoporosis. In recent years, the adverse effects caused by anabolic anti-osteolytic drugs have increased the interest of researchers in the potential therapeutic and preventive effects of natural plant derivatives and natural compounds against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 97 publications
(108 reference statements)
0
9
0
Order By: Relevance
“…Here, miR-146a potently inhibited in vitro and in vivo osteoclast formation, which may be attributed to the same downregulating effect on TRAF6. 37 , 38 This result suggested the therapeutic potential of MSNs in bone regeneration with an inflammatory microenvironment through regulation of the osteogenesis-osteoclasis balance.…”
Section: Discussionmentioning
confidence: 84%
“…Here, miR-146a potently inhibited in vitro and in vivo osteoclast formation, which may be attributed to the same downregulating effect on TRAF6. 37 , 38 This result suggested the therapeutic potential of MSNs in bone regeneration with an inflammatory microenvironment through regulation of the osteogenesis-osteoclasis balance.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have confirmed that abnormal activation of OCs can lead to progressive bone loss, which is the pathological basis of OP, and involves the influence and regulation of multiple signaling pathways (Qu et al 2022a , b ). Representative clinical anti-OP drugs mainly include bisphosphonates, estrogens, and calcitonin.…”
Section: Discussionmentioning
confidence: 89%
“…This study indicated that ISO has an excellent antioxidant effect and could prevent redox damage to cells through an Nrf2-related mechanism, which has stronger free radical scavenging activity than antioxidants and vitamin C (Brasil et al 2022 ; Yao et al 2012 ). Following appropriate stimulation, a signal transmitted from the cell membrane to the cytoplasm results in the dissociation of Nrf2 from Kelch-like ECH-associated protein 1 (Keap1) and its translocated to the nucleus, where it forms a co-activation complex with small Maf proteins to activate the expression of antioxidant-related genes and products, including CAT, GCLC, and HO-1 (Qu et al 2022a , b ; Yang et al 2022 ). In this study, we demonstrated that ISO dose-dependently inhibited intracellular ROS and suppressed osteoclast differentiation by upregulating the expression of Nrf2, promoting its nuclear translocation, and increasing the expression of related antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Consequently, various downstream signaling pathways are activated, including those of nuclear factor kappa B (NF-κB), mitogen-activated protein kinases (MAPK), phospholipase Cγ (PLCγ), and nuclear factor of activated T cells 1 (NFATc1). 6 As a result of transcriptional activation of these receptors consequently increased expression of genes specific to osteoclasts, such as TRAP, osteoclastspecific transmembrane protein (OC-STAMP), osteoclast-associated receptor (OSCAR), dendritic cell-specific transmembrane protein (DC-STAMP), calcitonin receptor (CTR), β3-integrin, ATP6v0d2, and cathepsin K (Ctsk). 7 Moreover, the generation of reactive oxygen species (ROS) induced by RANKL also contributes significantly to the activation of NF-κB and NFATc1, which promote osteoclast differentiation.…”
mentioning
confidence: 99%